China’s Road To Zero Hunger: Implementasi Sustainable Development Goals Dalam Memenuhi Food Security di Republik Rakyat Tiongkok - Pardede, Benjamin Juliano; Pattipeilohy, Shary Charlotte Henriette (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
After the end of the Millennium Development Goals, existing countries began to make a new formulation to continue sustainable development. The results of the new formulation that will continue the MDGs called Sustainable Development Goals which are now became the standard for countries in conducting sustainable development. A country's compliance with SDGs itself can be seen from how a country implements the SDGs in order to achieve the goals that have been formulated. DNV GL, an innovation and technology based company makes a prediction of the possibility of achieving the goals in the SDGs and turns out that China has a green indicator in the second goal, Zero Hunger. This study intends to explain the efforts made by China in achievingthe second goal of the SDGs and fulfilling the food security of the country. This research will use the concept of policy implementation that will analyze the factors that contribute to the realization of a policy such as policy standards and policy objectives, resources, economic, social, and political environment that supports China in carrying out the policies that have been designed. In addition, this research will also use the concept of food security namely availability, accessibility, utilization and stability to see whether China has fulfill the food security in the country. This study found that agricultural modernization and the green industry conducted by China have standards and policy objectives, resources, economic, social, political environment that supports the achievement of SDGs. However, China has not fulfilled food security in its country because haven’t fulfill all of the indicators from food security.